A Hierarchal Clustered Based Proactive Caching in NDN-Based Vehicular Network - Khan, Muhammad Yasir; Adnan, Muhammad; Iqbal, Jawaid; ul Amin, Noor; Roh, Byeong Hee; Ali, Jehad (Computer Systems Science and Engineering, 2023)
An Information-Centric Network (ICN) provides a promising paradigm for the upcoming internet architecture, which will struggle with steady growth in data and changes in accessmodels.Various ICN architectures have been designed, including Named Data Networking (NDN), which is designed around content delivery instead of hosts. As data is the central part of the network. Therefore, NDN was developed to get rid of the dependency on IP addresses and provide content effectively. Mobility is one of the major research dimensions for this upcoming internet architecture. Some research has been carried out to solve the mobility issues, but it still has problems like handover delay and packet loss ratio during real-time video streaming in the case of consumer and producer mobility. To solve this issue, an efficient hierarchical Cluster Base Proactive Caching for Device Mobility Management (CB-PC-DMM) in NDN Vehicular Networks (NDN-VN) is proposed, through which the consumer receives the contents proactively after handover during the mobility of the consumer. When a consumer moves to the next destination, a handover interest is sent to the connected router, then the router multicasts the consumer's desired data packet to the next hop of neighboring routers. Thus, once the handover process is completed, consumers can easily get the content to the newly connected router. A CB-PCDMM in NDN-VN is proposed that improves the packet delivery ratio and reduces the handover delay aswell as cluster overhead. Moreover, the intra and inter-domain handover handling procedures in CB-PC-DMM for NDN-VN have been described. For the validation of our proposed scheme, MATLAB simulations are conducted. The simulation results show that our proposed scheme reduces the handover delay and increases the consumer's interest satisfaction ratio. The proposed scheme is compared with the existing stateof- the-art schemes, and the total percentage of handover delays is decreased by up to 0.1632%, 0.3267%, 2.3437%, 2.3255%, and 3.7313% at the mobility speeds of 5 m/s, 10 m/s, 15 m/s, 20 m/s, and 25 m/s, and the efficiency of the packet delivery ratio is improved by up to 1.2048%, 5.0632%, 6.4935%, 6.943%, and 8.4507%. Furthermore, the simulation results of our proposed scheme show better efficiency in terms of Packet Delivery Ratio (PDR) from 0.071 to 0.077 and a decrease in the handover delay from 0.1334 to 0.129.
Keywords: Caching; Device mobilities; Handover delay; Hierarchical architectures; Information Centric Networks; Internet architecture; Named data networkings; Packet delivery ratio; Proactive caching; Vehicular networks; caching; hierarchical architecture; named data networking; Vehicular network